Readiness for technology based teaching among undergraduates of faculty of education, University of Colombo - Ranawaka, R.A.T.K.G.; Ranathunga, Y.S.; Sudarvannan, N.; Karunathilake, I.M. (South-East Asian Journal of Medical Education, 2020)
Introduction: Technology-based teaching is introducing new pedagogical methods or developing existing ones using Information and Communication Technology (ICT) with the aid of modern electronic media in order to fulfill the educational requirements. In this study, the level of readiness of pre-service teachers was assessed under technological competency, pedagogical competency and technological pedagogical competency which were developed based on the TPACK framework developed by Mishra & Koehla (2006). Method: Descriptive cross sectional study with an analytical part (correlation) was done at the Faculty of Education, University of Colombo with 196 undergraduates. Results: The participants showed high level of readiness related to all the three domains considered, 40.3% related to technological competency,40.67% related to pedagogical competency and 41.4% related to technological pedagogical competency respectively. There was no statistically significant difference between the two academic years related to all three domains considered. There is a strong linear correlation between the level of readiness for technology based teaching related to technological competency and the level of readiness for technology based teaching related to technological pedagogical competency (correlation coefficient=0.78). The correlation between pedagogical competency and technological pedagogical competency is moderately linear. (Correlation coefficient=0.41). Conclusion: The level of readiness for technology based teaching among undergraduates of Faculty of Education, University of Colombo is in a satisfactory level related to all three domains considered.
Keywords: Teaching; TPACK; Pre-service; Technology; Education